Negotiating Wonhan: Cognitive Frameworks and Ritual Responses to Unresolved Grievances in Joseon Korea - Kim, Yuri (Religions, 2025)
This study examines how cognitive mechanisms shaped the understanding and ritualization of wonhan (寃恨, resentment) in Joseon Korea, particularly in the context of disasters. Drawing on cognitive science and historical analysis, it demonstrates that while wonhan functioned as a shared conceptual framework across social boundaries, debates over wonhon (寃魂, resentful spirits) exposed ideological tensions in state orthodoxy. Through an analysis of key historical cases, particularly the 1451 Sinmi Year Rituals, the study shows how the tension between intention-based and system-based reasoning was negotiated within ritual practices and political discourse. The research reveals that state rituals, especially yeoje, served as sites where these competing reasoning modes interacted. Even as state officials maintained system-based interpretations of resentment as disruptive energy, the inherently anthropomorphic nature of ritual prayer necessitated treating the deceased as intentional agents. This created a practical synthesis of divergent reasoning modes within ritual contexts. By examining the cognitive foundations of wonhan and wonhon, this study highlights the multilayered nature of contentious religious issues. It demonstrates how shared conceptual ground can emerge even within seemingly opposed perspectives and how conflicting reasoning modes can coexist in ritual contexts. The findings suggest that religious disputes are not solely doctrinal conflicts but also reflect deeper cognitive tendencies that shape divergent interpretations.